Правове забезпечення екологічної безпеки: національний та міжнародний аспект - Коваленко, І.; Райниш, Н.; Kovalenko, I.; Rainysh, N. (Східноєвропейський національний університет імені Лесі Українки, 2018)
У статті узагальнено основні підходи щодо визначення поняття екологічної безпеки, її мету та завдання, а також проаналізовано сучасний стан правового забезпечення екологічної безпеки на національному та міжнародному рівні. Автори зробили висновки про необхідність докорінної зміни ставлення людей до питань охорони довкілля та раціонального використання природних ресурсів; необхідність об'єднання зусиль всіх країн світу для подолання сучасної екологічної кризи; удосконалення існуючої та створення нової нормативно-правової бази для забезпечення екологічної безпеки. The article summarizes and comments on the main approaches to the definition of the concept of ecological safety, its goals and tasks, and reveals the current state of legal provision of environmental safety at the national and international levels. The in-depth analysis of the issue provides the grounds to draw a conclusion that national and international security is impossible without taking into account the environmental factor. In terms of a global approach to security, any aspect that threatens the survival of the planet and its nature must be considered as a safety threat. The emphasis is laid on the hotly debated environmental problems at the national and international levels that slow down, and sometimes even make the process of solving environmental problems and ensuring environmental safety impossible. The burning issues to be solved urgently are: 1) radical change in the attitude of people towards environmental issues and the rational use of natural resources; 2) uniting the efforts of all countries to overcome the current environmental crisis in the world; 3) improving the existing and creating a new regulatory framework for environmental safety.
Legal Protection of Ecological Safety: National and International Aspects
Keywords: екологічна безпека; правове регулювання; навколишнє природнє середовище; екологічна обстановка; екологічна небезпека; ecological safety; legal regulation; the environment; ecological situation; ecological danger